T3SEdb: data warehousing of virulence effectors secreted by the bacterial Type III Secretion System - KHAN, MOHAMMAD ASİF; Tay, Daniel Ming Ming; Govindarajan, Kunde Ramamoorthy; KHAN, MOHAMMAD ASİF; Ong, Terenze Yao Rui; Samad, Hanif M.; Soh, Wei Wei; Tong, Minyan; Zhang, Fan; Tan, Tin Wee (My University, 2010)
Background: Effectors of Type III Secretion System (T3SS) play a pivotal role in establishing and maintaining pathogenicity in the host and therefore the identification of these effectors is important in understanding virulence. However, the effectors display high level of sequence diversity, therefore making the identification a difficult process. There is a need to collate and annotate existing effector sequences in public databases to enable systematic analyses of these sequences for development of models for screening and selection of putative novel effectors from bacterial genomes that can be validated by a smaller number of key experiments.